Da escassez do hidrocarboneto à abundância do ponto zero: Conhecendo o caminho para a sustentabilidade energética - Rosane S. Lourenço (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The scope of this study is comprehensive, extending from technological development to historical evolution of planning in energy sector. On policy, the current situation of the national context was clarified, including reforms and programs that characterized the industry in the last two decades. The adherence of Brazilian policy to the evolution of the energy and climate policies at the international level was obtained with the examination of more than ten countries and with the chronological comparison of the regulatory framework in Brazil, the United States and the European Union. The most interesting, however, was to see how planning and policy can be shaped by technical progress, albeit belatedly. This finding followed the examination of the technological dimension, divided in twelve branches of energy generation, which allowed a glimpse of the diversity of alternatives, as well as the real chances of achieving truly sustainable technologies.
Keywords: O33; 330; sustainable energy; renewable and non-renewable; political transition; technological innovations